The nutritional regulation of oocyte quality and early embryo development in cattle - Adamiak, Sylwia J. (2006)
The importance of nutrition on reproductive performance is well recognised. However,the mechanisms and specific factors regulating their interaction are still poorly understood. Interest has recently intensified, as fertility in dairy cows has declined. There is a body of evidence on the negative effects of reduced body condition, the high levels of energy and protein intake, however, the results are inconsistent between studies and the role of specific factors, such as insulin and leptin, in the regulation of ovarian function in cattle remains unclear. The main objective of this thesis, therefore, was to test the effects of animal body composition, planes of nutrition and diet composition with emphasis on endocrine and metabolic factors, including progesterone, oestradiol, insulin, IGF-I and leptin, on oocyte quality and early embryo development in cattle. This thesis has demonstrated that alterations in planes of nutrition (Maintenance (M) vs twice maintenance (2M)) affected oocyte quality, and that the effects were dependent on animal body condition score (BCS) (Low vs Moderate). Whilst high (2M) levels of feeding were beneficial for oocytes from animals in Low BCS, they were detrimental to oocyte quality for animals in Moderate BCS. Furthermore, the combination of feeding level and animal BCS created low (10 ull.J/ml), moderate (20 ).lIU/ml) and high (40).lIU/ml) plasma insulin concentrations. Inevitably, however, it also led to the creation of three corresponding levels of plasma leptin concentrations (low: 2 ng/ ml, moderate: 4 ng/ml, and high: 7 ng/ml), indicating that the effects of these metabolic hormones on ovarian function cannot be separated in vivo. However, there was no correlation between changes in metabolic hormones and oocyte quality, suggesting that other endocrine or metabolic factors, not recorded in this study, may be involved in determining the post-fertilisation developmental competence of oocytes. Animal body composition also played an important role in the dietary-induced modifications to oocyte developmental competence both in vivo and in vitro. Indicated by post-fertilisation development in vitro, oocyte quality was enhanced in Low BCS heifers offered the Fibre than the Starch based diets (43.6 vs 24.6% blastocysts for Fibre vs Starch diet), whereas inclusion of protected lipid reduced oocyte developmental competence (27.7 vs 42.9% blastocysts for presence vs absence of Megalac). However, in Moderate BCS heifers, diet composition had litde effect on oocyte quality. Although dietary treatments had little effect on endocrine profile, elevated plasma leptin concentrations were consistently correlated (P<0.001) with increased animal body fatness. The effects of dietary treatments on oocyte maturation in vivo, however, varied from those observed when sera from these animals were used during the final stages of oocyte maturation in vitro, and during early embryo development. These findings suggest that while some diets may be beneficial to oocyte development, they could have a negative effect on embryo quality and subsequent survival. Interestingly, serum harvested from Low BCS heifers enhanced blastocyst formation in vitro compared to serum from heifers in Moderate BCS (24.2 vs 19.0%). This indicates that animal BCS is an important factor involved in the regulation of not only oocyte quality, but also early embryo development. The reasons for these discrepancies between BCS groups, however, remain unknown. Finally, this thesis produced an interesting and novel insight into the nutritional regulation of the lipid content and fatty acid composition of bovine plasma, granulose cells (GCs) and cumulus-oocyte complexes (COCs), and also the effects of serum from contrasting nutritional backgrounds on the lipid content and fatty acid composition of embryos. In general, the inclusion of supplemental fatty acids in the diet significantly increased the lipid content of all tissues tested. The fatty acid composition of COCs and embryos, however, was not correlated with their quality. Nevertheless, differences in the fatty acid composition of plasma, GCs and COCs indicated that there is a selective mechanism of fatty acid uptake by the follicle compartment, which has a preference for saturated fatty acids. The importance and function of specific fatty acids in determining oocyte and embryo quality remain to be elucidated. This thesis has therefore demonstrated that animal body composition is an important factor determining the effects of feeding level and diet composition on oocyte and early embryo development. In summary, high levels of feeding and the Fibre based diets can enhance oocyte quality in thin, but not in moderately fat animals. Alterations in plasma insulin and leptin concentrations did not appear to be correlated with oocyte quality in the present studies, indicating that other factors, not monitored in this project, are possibly involved in the regulation of oocyte developmental competence.